Declining incidence of acromioplasty in Finland - Paloneva, Juha; Lepola, Vesa; Karppinen, Jaro; Ylinen, Jari; Äärimaa, Ville; Mattila, Ville M (ACTA ORTHOPAEDICA, 2015)
Background and purpose - An increased incidence rate of acromioplasty has been reported; we analyzed data from the Finnish National Hospital Discharge Register. Patients and methods - During the 14-year study period (1998-2011), 68,877 acromioplasties without rotator cuff repair were performed on subjects aged 18 years or older. Results - The incidence of acromioplasty increased by 117% from 75 to 163 per 105 person years between 1998 and 2007. The highest incidence was observed in 2007, after which the incidence rate decreased by 20% to 131 per 105 person years in 2011. The incidence declined even more at non-profit public hospitals from 2007 to 2011. In contrast, it continued to rise at profit-based private orthopedic clinics. Interpretation - We propose that this change in clinical practice is due to accumulating high-quality scientific evidence that shows no difference in outcome between acromioplasty and non-surgical interventions for rotator cuff disease with subacromial impingement syndrome. However, the exact cause of the declining incidence cannot be defined based solely on a registry study. Interestingly, this change was not observed at private clinics, where the number of operations increased steadily from 2007 to 2011.